(untitled) (International Journal of Engineering and Computer Science, 2017)
The second most common cancer among world women is breast cancer. We have many categorize of breast cancer. About 40000 women die for this cause in resent year[1]. We consider the relationship between happiness and life expectancy with death anxiety in patients with breast cancer. In this article we use logistic regression in R. Results show us that by increasing the awareness and understanding of people’s beliefs about this disease, they can increase the ways of happiness and life expectancy in these people which reduces the anxiety of death in these patients.